CD4+ T cells with an activated and exhausted phenotype distinguish immunodeficiency during aviremic HIV-2 infection. (23rd October 2016) - Buggert, Marcus; Frederiksen, Juliet; Lund, Ole; Betts, Michael R.; Biague, Antonio; Nielsen, Morten; Tauriainen, Johanna; Norrgren, Hans; Medstrand, Patrik; ,; Karlsson, Annika C.; Jansson, Marianne
Abstract : Supplemental Digital Content is available in the text Abstract : Objective: HIV type 2 (HIV-2) represents an attenuated form of HIV, in which many infected individuals remain 'aviremic' without antiretroviral therapy. However, aviremic HIV-2 disease progression exists, and in the current study, we therefore aimed to examine if specific pathological characteristics of CD4 + T cells are linked to such outcome. Design: HIV-seronegative ( n = 25), HIV type 1 (HIV-1) ( n = 33), HIV-2 ( n = 39, of whom 26 were aviremic), and HIV-1/2 dually (HIV-D) ( n = 13)-infected study participants were enrolled from an occupational cohort in Guinea-Bissau. Methods: CD4 + T-cell differentiation, activation, exhaustion, senescence, and transcription factors were assessed by polychromatic flow cytometry. Multidimensional clustering bioinformatic tools were used to identify CD4 + T-cell subpopulations linked to infection type and disease stage. Results: HIV-2-infected individuals had early and late-differentiated CD4 + T-cell clusters with lower activation (CD38 + HLA-DR + ) and exhaustion programmed death-1 (PD-1) than HIV-1 and HIV-D-infected individuals. We also noted that aviremic HIV-2-infected individuals possessed fewer individuals. CD4 + T cells with pathological signs compared to other HIV-infected groups. Still, compared to HIV-seronegative individuals, aviremic HIV-2-infected individuals had T-bet + CD4 + T cells that showed elevated immune activation/exhaustion, and particularly the frequencies of PD-1 + cells were associated with a suboptimal percentage of CD4 + T cells. Conclusion: Increased frequencies of CD4 + T cells with an activated/exhausted phenotype correlate with exacerbated immunodeficiency in aviremic HIV-2-infected individuals. Thus, these findings encourage studies on the introduction of antiretroviral therapy also to individuals with aviremic HIV-2 infection.